2011
DOI: 10.1074/jbc.m111.277038
|View full text |Cite
|
Sign up to set email alerts
|

CXCR7/CXCR4 Heterodimer Constitutively Recruits β-Arrestin to Enhance Cell Migration

Abstract: G protein-coupled receptor hetero-oligomerization is emerging as an important regulator of ligand-dependent transmembrane signaling, but precisely how receptor heteromers affect receptor pharmacology remains largely unknown. In this study, we have attempted to identify the functional significance of the heteromeric complex between CXCR4 and CXCR7 chemokine receptors. We demonstrate that co-expression of CXCR7 with CXCR4 results in constitutive recruitment of ␤-arrestin to the CXCR4⅐CXCR7 complex and simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
328
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 303 publications
(352 citation statements)
references
References 65 publications
13
328
2
1
Order By: Relevance
“…Conformational rearrangement of the partners in a heterodimeric complex can alter ligand binding (49,50) and affect ligand function (42,51) by modulating their ability to activate G proteins (43,50). Here, we show evidence that CCR5 coexpression and receptor oligomerization impede gp120 IIIB binding to target cells.…”
Section: Discussionmentioning
confidence: 72%
“…Conformational rearrangement of the partners in a heterodimeric complex can alter ligand binding (49,50) and affect ligand function (42,51) by modulating their ability to activate G proteins (43,50). Here, we show evidence that CCR5 coexpression and receptor oligomerization impede gp120 IIIB binding to target cells.…”
Section: Discussionmentioning
confidence: 72%
“…This is also consistent with the observations of Gambaryan et al (13), who demonstrated that the CXCR4 antagonist AMD3100 inhibited hypoxia-induced pulmonary vascular remodeling in an adult model and showed synergistic effects when combined with a CXCR7 antagonist. This latter finding is particularly relevant, given the data suggesting that the CXCR7/CXCR4 heterodimer potentiates SDF-1-mediated downstream β-arrestindependent cell signaling pathways (33). It should be noted, however, that although Gambaryan et al did not observe any significant effects on pulmonary vascular remodeling following the administration of the CXCR7 antagonist alone, differences in the age and strain of mice (the C57/BL6 strain used in Gambaryan's study is genetically deficient in the gene for the CXCR7 ligand CXCL11; ref.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the GPCRs, activated G␣ i or G␣ 13 subunits, other GPCR accessory proteins, such as GRK2 and ␤-arrestin, or the regulators of G proteins signaling (RGS proteins) G␣ 13 , are not required to mediate directional chemotaxis of neutrophils in solution. Numerous reports have suggested G␣ subunits along with RGS, GRK2, and ␤-arrestin to play a role in migration (12)(13)(14)(15)(16)(17), but these proteins may serve to modulate G␤␥-mediated chemotaxis. A recent report suggested that there is a role for G␣GDP in directing cell migration that could be involved in 12155-mediated signaling and could be the subject for further investigation (36).…”
Section: Discussionmentioning
confidence: 99%